Kualitas dan Daya Terima Nagasari Padat Gizi sebagai Makanan Anak Balita - Amanah, Sary; Baidar, Baidar; Yulastri, Asmar (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research aimed to analyze the quality and to know capacity ofacceptance nutrient dense nagasari as a food toddlers. The research was thedevelopment of research. The object of research was a nutrient dense nagasari asa toddlers. The procedure to begins with a quality test using organoleptic test.Test of Organoleptic conducted by involving six professional panelists people isexperts in area of culinary, nutrition and food, and then do the test of capacityacceptance to 24 toddlers in kindergarten Dharmawanita UNP. Result of qualitytest nagasari which developed is said valid by professional panelists people on thefourth trial because the results of assessment professional panelists people ineach indicator have very good that is, 5.00. Furthermore, the result of capacityacceptance test showed that nagasari which developed is received by toddlers.Key word: Qualitty, capacity acceptance, nagasari, nutrient denseÂ¹